Preventive Conservation Of The Weapons At The Central Museum Of The Indonesian National Army Force (TNI AD) “Dharma Wiratama” Yogyakarta - Maulana Ibrohim; Yohana Ari Ratnaningtyas; Dian Ajeng Kirana (Institut Seni Indonesia Yogyakarta, 2023)
The Central Museum of the Indonesian National Army Dharma Wiratama Army is one of the museums whose management is under the auspices of the Army and whose direction is managed by the Central Museum and Monuments of the Army History Service. The primary collection is the longbarreled weapons used by the Army during the era of independence until now. Preventive conservation is a conservation action categorized as the most essential action or category. Museum staff can carry out preventive conservation without having to study this knowledge in depth. This research was carried out to determine how preventive conservation actions or activities were carried out on the weapons collection at the Dharma Wiratama TNI AD Museum. They are using qualitative methods with a case study type. Interviews, observation, and document study are the data collection methods used in this research. The research results show that several agents of damage occur in museums, namely physical forces and theft, pollutants, humidity, ultraviolet light, and temperature. Preventive conservation actions or activities by the Dharma Wiratama TNI AD Museum. Includes security, controlling temperature, humidity, lighting, and moving or transporting collections.